Tuberculosis related Neuroretinitis and Retinal Vasculitis in an Immunocompetent Patient - Goel, Neha (Nepalese Journal of Ophthalmology, 2021)
Introduction: This study aimed to describe the occurrence of bilateral neuroretinitis and retinal vasculitis in an immunocompetent female with disseminated tuberculosis.Case description: A 25 year old female diagnosed with disseminated tuberculosis presented with sudden painful loss of vision bilaterally. On examination she was found to have bilateral neuroretinitis and retinal periphlebitis involving the posterior pole. She was prescribed systemic steroids in addition to the anti-tuberculous therapy that she was receiving. The fundus lesions gradually resolved over four months with modest improvement in visual acuity. There were no recurrences in the follow up period of 14 months. Conclusions: Ocular involvement in the form of neuroretinitis with concomitant retinal vasculitis can occur in patients with disseminated tuberculosis. Addition of systemic steroids to anti-tuberculous therapy leads to anatomical resolution with improvement in visual acuity.